Biodisk study as domestic wastewater secundary treatment - Delgado, Gustavo (2019)
Laboratory model RBC system was designed as secondary treatment of an UASB reactor effluent. RBC System was built with two stages in series, each stage with effective volume of 81 liters and seven (07) PVC disks of 60 cm diameter with a total effective area of ​​7.92 m2. RBC system operated at a constant flow rate of 432 l / day (HRT of 4.50 hours) and was operated in two periods at different disk rotational speed (3 rpm for 4 months and 5 rpm for 3 months). The values ​​of BOD5, SST, Turbidity, pH and Temperature were measured. Moreover, the physical and microbiological biofilm characteristics were observed throughout the study period. RBC System achieved optimal degree of oxygenation, with an average value of 5.21 mg DO/ l just in the first stage. DOB5 Removal efficiency was 90% for 5 rpm of rotational speed and 78% for 3 rpm. Finally, the RBC system showed a better performance in terms of organic matter removal for 3 rpm rotational speed of. Moreover, it was found that two stages performance in series was higher than a single stage. The most representative biofilm microorganisms in first stage were protozoa ciliated swimmers or free and filamentous bacteria that had an excessive growth at second period. In the second stage, it was fixed ciliated protozoa, rotifers and unicellular and filamentous algae.